Penerapan Model Picture And Picture Dalam Meningkatkan Motivasi Dan Hasil Belajar IPA - Darma, Eriani (JURNAL GLOBAL EDUKASI, 2018)
Abstract: This study aims to improve the motivation and learning outcomes of class VII.1 of SMP Negeri 12 Pekanbaru by applying the model of picture and picture to the material of Diversity of Living Beings. The study was conducted in February-April 2016 with the research subjects being 38 students of class VII.1 12 Pekanbaru State Junior High School in the 2016/2017 school year. Learning outcomes in the cognitive and affective domains were obtained from the posttest results as well as observation sheets. Learning motivation results were obtained from the results of the initial questionnaire and the final questionnaire. The results of the study were analyzed using mixed data analysis (quantitative and qualitative). The results showed that the application of the model of picture and picture on the material of Diversity of Living Beings could improve: (1) Student learning outcomes in the material Diversity of Living Beings with the acquisition of learning outcomes in the cognitive domain from an average score of 60.42 first cycle to 80.42 in the cycle second and the percentage of achievement of KKM from 65.79% in cycle first to 86.84% in cycle second and affective domain learning outcomes 0% in cycle first to 60% and (2) Motivation to learn students on material Diversity of Living Beings with a high category increase from 69.56% to 100%. Keyword: picture and picture, learning outcomes, learning motivation, classification of living things Abstrak: Penelitian ini bertujuan untuk meningkatkan motivasi dan hasil belajar siswa kelas VII.1 SMP Negeri 12 Pekanbaru dengan menerapkan model picture and picture pada materi Keanekaragaman Makhluk Hidup. Penelitian dilaksanakan pada bulan Februari-April 2016 dengan subyek penelitian adalah 38 siswa kelas VII.1 SMP Negeri 12 Pekanbaru tahun pelajaran 2016/2017. Hasil belajar ranah kognitif dan ranah afektif diperoleh dari hasil posttest juga lembar observasi. Hasil motivasi belajar diperoleh dari hasil lembar kuisioner awal dan kuisioner akhir. Hasil penelitian dianalisis dengan menggunakan analisis data campuran (kuantitatif dan kualitatif). Hasil penelitian menunjukkan bahwa penerapan model picture and picture pada materi Keanekaragaman Makhluk Hidup dapat meningkatkan: (1) Hasil belajar siswa pada materi Keanekaragaman Makhluk Hidup dengan perolehan hasil belajar ranah kognitif dari rata–rata skor siklus I 60,42 menjadi 80,42 di siklus II dan persentase pencapaian KKM dari 65,79 % di siklus I menjadi 86,84% di siklus II serta hasil belajar ranah afektif 0 % pada siklus I menjadi 60 % dan (2) Motivasi belajar siswa pada materi Keanekaragaman Makhluk Hidup dengan peningkatan kategori tinggi dari 69,56 % menjadi 100%. Kata kunci: picture and picture, hasil belajar, motivasi belajar, klasifikasi mahluk hidup